Impaired drainage of vein of Labbé following venous sinus stenting for idiopathic intracranial hypertension. (15th September 2018) - Boddu, Srikanth R; Gobin, Y Pierre; Dinkin, Marc; Oliveira, Cristiano; Patsalides, Athos
Abstract : Purpose: The impact of venous sinus stenting (VSS) on vein of Labbé (VOL) drainage is poorly understood. The purpose of the study is to examine the incidence and potential high risk factors of impaired VOL drainage among idiopathic intracranial hypertension (IIH) patients following VSS. Materials and methods: Institutional review board approved prospective evaluation of all IIH patients who underwent VSS over a 5 year period (January 2012 to December 2017) at Weill Cornell Medical Center constituted the study population. Patient demographics, procedural details (laterality of stenting, balloon angioplasty, number of stents, and stent diameters), morphology of the VOL and changes in the flow in the VOL, type of sinus stenosis, and transverse sinus symmetry were evaluated. We used χ 2 analysis to evaluate impaired VOL drainage against other variables. Statistical significance was set at 0.05. Results: 70 consecutive patients (67 women, 3 men) with a mean age of 31±9.8 years underwent VSS. Stenosis was extrinsic in 63% (n=44) and intrinsic in 37% (n=26) of patients. Impaired drainage of the VOL was detected in 9/70 (13%) patients. Ipsilateral VOL was recognized as dominant in 20% (n=14), co-dominant in 51% (n=36), and non-dominant in 29% (n=20) of patients. Impaired VOL drainage was significantly associated with ipsilateral VOL dominance (P=0.001) and stent diameter of ≥9 mm (P=0.042). All patients demonstrated widely patent VOL on follow-up contrast enhanced MR venography at 3 months and 24 months. Conclusion: Impaired drainage of the ipsilateral VOL is a potential consequence of VSS with 13% incidence, and has significant association with ipsilateral superficial cortical venous drainage via dominant VOL and stent diameter of ≥9 mm. Clinical trial registration: NCT01407809 .